2004
DOI: 10.1103/physreva.69.052718
|View full text |Cite|
|
Sign up to set email alerts
|

Elastic resonant and nonresonant differential scattering of quasifree electrons fromB4+(1s)and

Abstract: High-resolution doubly differential cross-section measurements and calculations for quasifree electrons elastically scattered through 180°from ground-state He-and H-like boron ions are presented. The measurements, covering the entire (for B 3+ ) and (for B 4+ ) Rydberg series populated by resonant excitation, were performed by zero-degree Auger projectile electron spectroscopy of 3.91 MeV B 4+ and 3.08-7.48 MeV B 3+ ions in collisions with H 2 targets. The projectile energy dependence study is used to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 105 publications
(183 reference statements)
3
20
1
Order By: Relevance
“…Recently, this enhancement of the 1s2s2p 4 P states was determined more quantitatively for 1.1 MeV/amu F 7+ (1s2s 3 S) impact on He and Ne [3]. For the case of He it was found that the measured ratio R = 4 P /( 2 P − + 2 P + ) was 2.9, 1 which has to be compared to the value of 2 expected from spin statistics [4][5][6].…”
Section: Introductionmentioning
confidence: 92%
“…Recently, this enhancement of the 1s2s2p 4 P states was determined more quantitatively for 1.1 MeV/amu F 7+ (1s2s 3 S) impact on He and Ne [3]. For the case of He it was found that the measured ratio R = 4 P /( 2 P − + 2 P + ) was 2.9, 1 which has to be compared to the value of 2 expected from spin statistics [4][5][6].…”
Section: Introductionmentioning
confidence: 92%
“…In our recent publication [30], the long-standing problem of how multi-unpaired-electron ion cores behave, while undergoing electron processes during fast atomic collisions, was treated both experimentally and theoretically. A viable way to explore this is to consider the 2p SEC channel in MeV collisions (Equation (36)). There, the ratio R of the similarly configured 1s2s2p 4 P to 2 P ± SEC cross sections, defined by Equation (37), should bear the corresponding population spin statistics signature.…”
Section: Spin Statistics-ratio R Of 1s2s2p 4 P To 2 P Cross Sectionsmentioning
confidence: 99%
“…In the case of 2p single electron capture (SEC) in collisions of 1s2s 3 S ions with He and H 2 , R has been considered to be an indicator of spin statistics [31][32][33][34][35]. Indeed, this ratio results in R = 1, when considering only spin multiplicity, while R = 2 in the frozen core approximation, where only the 4 P and a single 2 P state can be produced from the 1s2s 3 S initial state [34,36,37]. Such statistical arguments and approximations are often used to simplify difficult problems of computing relative populations in high energy plasmas [4] and can therefore be of important practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, identification of K-Auger transitions from singly and multiply charged ionic states of boron has been performed experimentally by using electron spectroscopy in ion-atom collisions [40][41][42][43], photon absorption and emission by laser-produced plasmas [44,45], EII [46], beam-foil spectroscopy [47], high-resolution spark spectroscopy [48] and high-resolution PI spectroscopy employing synchrotron radiation [22]. Theoretically, resonance energies and linewidths for Auger transitions in the Be-like boron ion have been calculated using a variety of methods, such as 1/Z perturbation theory [49][50][51], unrestricted Hartree-Fock [52], configuration interaction for initial and final states [53], single or multi-configuration Dirac-Fock [45], the saddle-point-method (SPM) with Rmatrix or complex coordinate rotation methods [54][55][56][57][58], complex scaling, multi-reference configuration interaction (MR-CI) [59] the spin-dependent localized Hartree-Fock density-functional approach [60] and R-matrix theory [61].…”
Section: Introductionmentioning
confidence: 99%